กรอบในเนื้อหาเชิงลบของหนังสือพิมพ์เกี่ยวกับรัฐบาล ช่วงปลายสมัยรัฐบาลบรรหาร ชวลิต และชวน - กระสุน สกุลโพน (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research compared the framing of negative contents about the Banharn, Chawalit and Chuan Administrations at the end of their periods. It looked specifically at the amount of the negative contents and how they were framed in each case. The news stories and articles on the three governments during the last 90 days of their periods in three daily newspapers namely Matichon, Thairath and Daily News were content analyzed. The results showed that there were more negative contents than positive and neutral contents at the end of each administration. However, the problems of the three administrations were framed differently as followed: - For the Banharn Administration, the problems were most often framed as being caused by the conflict in the administration and the uncertainty or the lack of trust in the administration respectively. - For the Chavalit Administration, the problems were most often framed as being the result of the uncertainty or the mistrust in the administration and the failure of his governance respectively. - For the Chuan Administration, the problems were most often framed as being the result of the inappropriate policy and the uncertainty or mistrust in the administration respectively. The research suggested that the differential treatments were due to characteristics of each government, the social context and variables related tothe newspapers.